MANAJEMEN PENILAIAN KINERJA GURU PAI DALAM KOMPETENSI GURU DI SMP IT ASY SYADZILI PAKIS MALANG - Shofiana Khoirunnisa; Abd Jalil; Fita Mustafida (VICRATINA, 2021)
Teacher performance assessment is carried out to realize professional teachers who are expected to contribute directly to the improvement of the quality of learning conducted. In the implementation of teacher performance assessment, of course, in carrying out the required good management in managing the implementation of teacher performance assessment to achieve the goals that have been set in addition to being able to organize the implementation of performance assessment in a structured manner can also produce maximum performance assessment results. The results of the maximum teacher performance assessment will provide convenience to evaluate some shortcomings in the implementation of teacher performance assessment. Kata Kunci: management, assessment of teacher performance, teacher competence